Conceptions on Interdisciplinarity between Teachers of the College Education (Global Journal of Human-Social Science, 2021)
With the implementation of Interdisciplinary Bachelor's degrees in Brazilian universities, new dynamics of teaching and research proved necessary, but few analyzes were made to better clarify the concepts about interdisciplinarity, present among teachers. This study aims to present a possibility of understanding on this topic, from the perspectives of some teachers who teach in interdisciplinary degrees. For that, the Free Word Association Test (TALP) was applied and semistructured interviews were conducted with them. The corpus was organized in Word, Wordle and Iramuteq and evaluated according to Bardin's Content Analysis. The results of this study corroborate and, at the same time, ratify the idea of interdisciplinarity as pluriconceptual and polysemic, covering from the simple to the most complex way of understanding the hyperdynamic structure of knowledge, in which we are faced with several possibilities of interpretation, understanding and practices they point, above all, to the subjects' attitudes, as evidenced by the basic literature about this theme.
Keywords: education; higher; concept formation; interdisciplinarity; universities